Kabuli Mustafa Efendi ve Kenzü’ l-esrar adlı eseri - Aydeniz, M. Fazıl (My University, 2001)
Kenzü'l-Esrâr li's-Sâlikîn adlı eser, 19 yy.'da Edirne'de yaşamış olan Kabûlî Mustafa Efendi tarafından yazılmıştır. Eser müellif tarafından kendisine sorulara cevap verme ve ayrıca tarîkattaki sâliklere bilgi verme amacıyla yazılmıştır. Müellife ifadesine göre kendisine sorulan sorular şunlardır: Tarîkattaki sülûkün hâlinden, ve sülûkle nefsin bilinmesinden ve insan vücûdunun hakîkatinden ve kâmil mürşidlerin sırları. Kenzü'l-Esrâr'da tasavvufî bir çok konu üzerinde durulmuştur. Bu konular: İnsanın hakîkati ve yaratılış, seyr u sülûk, nefsin mertebeleri, kalbin tavırları, ilm-i ledün, zikr-i cehrî(sesli), râbıta, mürşidin bilmesi gereken âdâb, sâlikin bilmesi ve uyması gereken âdâb, tarîkattaki âdâb, tarîkattaki dört kapı kırk makam, ehl-i beyt sevgisi ve on iki imam, tâc, hırka, post ve seccâde. Bu eserde Rifâî tarîkatına mensûb olan müellif tasavvûfî konularda ve tarîkat hakkında bilgi vermektedir. Eser osmanlıca olarak yazılmıştır ve değişik kütüphanelerde nüshaları vardır. Biz çalışmamız esnasında bu nüshalardan iki tanesinden faydalandık. Bu çalışmamızın amacı, 19. yy.'da Edirne'de yaşamış müellifin kaleminden bu döneme ait Rifâî tarîkatının âdâbı ve görüşlerini öğrenmek ve bu konuda çalışanlar için ulaşabilecekleri bir kaynak oluşturmaktır.

KABÛLÎ MUSTAFA AND HİS WORK ENTİTLED KENZÜ'L- ESRÂR The work named Kenzü'l-Esrâr li's-sâlikîn was written by Kabûlî Mustafa Efendi lived in Edirne in 19th century. The work was written in order to response the questions that was asked to the writer and inform the disciples of the religious way. According to the writer the questions that were asked to himself are these: the state of the following of the religious way and grasping the self with the help of this religious way, the reality of human body and the mysteries of the perfect spritual guides. İn Kenzü'l-Esrâr, many sufic (Islamic mysticism) subjects are mentioned: the reality and the nature of human being, the progress of the following the religious way, levels of the self, manners of the soul, inner science, reciting aloud God's name, devotion, the rules of manner that was necessary for the spritual guide to know, the rules manner that was necessary for disciple to know and obey, the rules of manner in the religious way, four gate fourthy authorities, the love for the family of Prophet Mohammed and twelve imam* crown (tâc), cardigan (hırka), hide (post) and prayer- rug (seccade). In this work, the writer who is a member of Rifâî religious way is giving information about sufic subjects and Rifâî way,. The work was written in Ottoman Turkish and its various capies can be found in different libraries. During our studying process we benefit from two capies. The object of our study is to know about the opinions and the rules of manner of Rifâî way which belongs to the 19th century; and to provide sources for the ones who are studying on this subject. * İmam: Religious leader.
Keywords: Akâid ve Kelâm; Din; Islam Dini-tasavvuf; İslam Dini; Tasavvuf